Agrilink: design and evaluation of an IoT-Based smart agriculture system for plant watering and humidification - Syafiq, Muhamad; Abd Halim, Muhamad Hazrin Fahmi; Zainuddin, Ahmad Anwar; Ahmad, Norhanim Fatihah; Rosdi, Nur Nisa Humairah; Mazlan, Farah (Penteract Technology, 2025)
Modern urban and small-scale agricultural practices often struggle with maintaining ideal plant growth conditions due to inconsistent care and inefficient water use. To address this issue, this study introduces Agrilink, an IoT-based automated plant watering and monitoring system designed to optimize plant care through real-time data collection and environmental control. The product utilizes ESP32 and ESP8266 microcontrollers integrated with various sensors—ultrasonic, soil moisture, and DHT22 temperature/humidity—to continuously monitor and manage the plant environment. The system comprises two primary components: a smart water control device that conserves water and a mist maker that sustains optimal humidity levels. Key data is displayed on a local LCD while a web dashboard provides users with convenient remote access and system insights. Testing revealed a 17.7% margin of error in humidity readings compared to commercial-grade sensors. Despite this limitation, Agrilink demonstrates significant potential for societal impact, especially in enhancing home gardening, supporting sustainable urban farming, and promoting efficient agricultural practices in water-scarce regions.